INVESTIGATING THE EFFICACY OF INTEGRATED DETECTOR AND PHOTON COUNTING APPROACHES FOR BREAST LESION DECOMPOSITION IN BREAST CANCER - Alumuku, L.; Iortile, J. T. (FUDMA JOURNAL OF SCIENCES, 2025)
The World Health Organization (WHO) reports that breast cancer is the primary cancer diagnosis for women worldwide, accounting for 11.7% of new cancer cases. In Nigeria, 49% of women 36 and above are diagnosed with breast cancer, ranking Nigeria second in Africa. The National Cancer Control Programme (NCCP) seeks to improve patient survival through early diagnosis using various screening modalities, including Computed Tomography (CT). This study explores spectral decomposition techniques for lesion contrast enhancement in breast CT, building on previous research that highlights the benefits of CT over 2-D mammography. The work featured in this paper presents an idealized scenario of noiseless images devoid of scatter or photon noise to investigate the intrinsic characteristics of contrast in CT imaging. A 2-D breast phantom with a diameter of 100mm was built and employed in photon counting methodology to simulate breast lesions. Three distinct experiments were conducted across photon energies in bins of 20keV, 10keV, 5kev and examined spectrally. The decomposition lesion showed substantially greater contrast of about 70% within the energy spectrum of 1-60 keV in comparison to conventional integrating CT methodologies. Contrast values have been attained at lower energy bins, which agrees with the promising features of photon counting technology for early detection of lesions and correlate with the attenuation of glandular tissues. The photon counting technique has exhibited potential for the visualization of synthetic images in bins predicated on contrast analyses.